KEABSAHAN PERJANJIAN KAWIN YANG TIDAK DICATATKAN DI KANTOR PENCATATAN SIPIL DAN AKIBAT HUKUMNYA TERHADAP PIHAK KETIGA (STUDI KASUS: PUTUSAN PENGADILAN TINGGI JAWA BARAT NOMOR: 449/PDT/2016/PT.BDG)” - Nicholas Alexandros; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
In marriage law, it regulates the issue of marriage agreements which aim to anticipate if in the future a divorce occurs, sometimes there is a struggle for property as well as the costs needed for children's educational needs or with third parties. “Through the Constitutional Court Decision No.69 / PUU-XIII / 2015, which basically confirms that marriage agreements must be registered to fulfill the element of publicity. But in fact in the case of the West Java High Court Decision Number: 449 / Pdt / 2016 / PT.BDG the marriage agreement was not registered with the Civil Registry Office. So that the problem arises: How is the validity of a marriage agreement that is not registered at the civil registration office? What is the legal effect on third parties by not recording the marriage agreement at the civil registration office? The results of this study indicate that there are still potential married couples who do not know that the marriage agreement they made before a notary must be registered at the civil registration office so that the marriage agreement binds a third party. Therefore, a marriage agreement that has been made by the prospective husband and wife must be registered at the civil registration office so that it binds a third party because if it is not recorded, the marriage agreement only binds the parties who made it.”